PEMODELAN SPESIASI Cr(VI) DI SUNGAI CODE YOGYAKARTA MENGGUNAKAN VISUAL MINTEQ DAN WASP - , HERDA DESMAIANI, Dr. Eko Sugiharto, DEA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Study related to Cr (VI) speciation modeling in Code River Yogyakarta using Visual Minteq to determine Cr(VI) species in Code River of Yogyakarta and pollutants impact prediction caused by activity of industry in river used WASP (Water Quality Analysis Simulation Program). In this research, it was studied the effect of pH on Cr (VI) species that has been formed as well as the influence of the presence of industry , Kd values , bottom roughness coefficient and river discharge to Cr (VI) concentration in the Code River . Modelling was done using the source data from the literature as well as related services. The result of modeling using Visual MINTEQ indicates Cr (VI) species in Code River is CrO dominantly as CrO .The concentration was increased, if the pH of the river was getting higher. HCrO give result that the industry would affect the water quality of Code River. It could be seen through the higher Cr (VI) concentration in the segmen 1 of the river. The concentration of was directly proportional to bottom roughness 4 2- , HCrO4 - , Cr2O7 2- and H2CrO4 . Species Cr(VI) 4 2 - 4 2 - would be formed, if pH value in the river was in acid condition. Modeling using WASP Cr (VI) the value of Kd and inversely proportional to the value of the . Cr (VI) concentration in dry season was higher than in rainy season.